Indian fiscal federalism at the crossroads: Some reflections - Larry Randall Wray (Levy Economics Institute of Bard College, 2019)
There is a growing recognition that fundamental changes are happening in Indian fiscal federalism ex post the abolition of the Planning Commission, the creation of the National Institution for Transforming India (NITI) Aayog, the constitutional amendment to introduce the Goods and Services Tax (GST), the establishment of the GST Council, and the historically high tax devolution to the states based on the 14th Finance Commission's recommendations. Recently, policymakers and experts have raised a few issues, including: whether or not to make Finance Commissions "permanent" or to abolish them by making the tax devolution share constant through a constitutional amendment; the need for an institution to redress spatial inequalities in order to fill the vacuum created by abolishing the Planning Commission; and making the case for Article 282 of the constitution to be circumscribed. The debates are also focused on whether there is a need to establish a link between the GST Council and Finance Commissions, and if India should devise a mechanism of transfer that is predominantly based on sharing of grants for equalization of services rather than tax sharing. Creating a plausible framework for debt-deficit dynamics while keeping the fiscal autonomy of states intact and ensuring output gap reduction and public investment at the subnational level without creating disequilibrium were also other matters of concern. These debates are significant, especially when a group of states came together for the first time ever to question the terms of reference of the 15th Finance Commission amid growing tensions in federal-state relations in India.
Keywords: H77; 330; Fiscal Federalism; Finance Commission; Revenue Sharing; Fiscal Equalization; Goods and Services Tax (GST); Public Debt; Fiscal Rules